2018
DOI: 10.3126/jngmc.v16i1.24219
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hypertension in Hemorrhagic Stroke at NGMCTH, Kohalpur

Abstract: Aim: To study the prevalence of hypertension in hemorrhagic stroke in patients admitted in medical units of Nepalgunj Medical College Teaching Hospital (NGMCTH), Kohalpur. Background : Hemorrhagic stroke has remained a serious disease despite recent advances in medical treatment. It is one of the most common emergencies encountered in clinical practice and predominantly effects elderly population leading to chronic disability and dependency. This study was designed to identify hypertension as a major cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The sample size of quantitative studies ranged from nine to 1017 participants. Studies were mainly published in national journals (n = 48) [ 10 – 21 , 23 – 35 , 37 , 39 , 41 – 43 , 45 – 56 , 58 60 , 63 , 64 ], and only seven studies were published in international journals [ 22 , 36 , 40 , 44 , 57 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The sample size of quantitative studies ranged from nine to 1017 participants. Studies were mainly published in national journals (n = 48) [ 10 – 21 , 23 – 35 , 37 , 39 , 41 – 43 , 45 – 56 , 58 60 , 63 , 64 ], and only seven studies were published in international journals [ 22 , 36 , 40 , 44 , 57 , 61 , 62 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-four studies reported the mean age of the patient population [ 10 , 12 – 14 , 19 23 , 26 28 , 30 , 31 , 33 , 36 – 41 , 45 , 48 , 50 – 53 , 56 , 57 , 59 , 60 , 62 – 64 ]. As indicated in Table 1 , the pooled mean age was 62.4 years, ranging from 51.9 [ 38 ] to 70.5 years [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations